PENERAPAN APLIKASI BIMBINGAN DAN KONSELING BERBASIS WEBSITE DI TINGKAT SMK : SEBUAH STUDI PUSTAKA - Tsulistia Poetry Hendrawan; Herdi Herdi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The method used in this research is a literature study by collecting several sources of previous research that discuss the same topic as the research to be conducted, namely from 6 journals. The purpose of this research is to describe how the implementation and benefits of the application of web-based guidance and counseling at the SMK level and to determine the effectiveness of using the application of website-based guidance and counseling at the SMK level. Based on the findings from 6 journals, it shows that the application of website-based guidance and counseling applications at the SMK level is very effective and good for application to students, because there are many conveniences for counseling teachers at school.